(3UjGfI h EOGeI fXe GdeYdheGJ GdEOGQjIs - (3eMeO(B, (3GdWGFjs ((3YeGf(B:s (3OGQ GdeSjQI ddfTQ h GdJhRjY(B,s, 2007)
(3jVe eQGMd OhQI JWhjQ fXe GdeYdheGJ GdEOGQjI, GdebUhO HUjGfI fXe GdeYdheGJ GdEOGQjI hCgejJgG hCgOGagG, eHQQGJ UjGfI fXe GdeYdheGJ hGdYhGed GdeQJHWI HgG, CfhGY UjGfI fXe GdeYdheGJ GdEOGQjI, JcGdja UjGfI fXe GdeYdheGJ GdEOGQjI, EOGQI YedjGJ UjGfI fXe GdeYdheGJ GdEOGQjI, UjGfI GdCLgRI hGdeYOGJ GdeSJNOeI aj JWHjbGJ fXe GdeYdheGJ GdEOGQjI, UjGfI GdHQeLjGJ hGdfXe, UjGfI GdTHcGJs
(3HjHdjhZQGajG(B: (3U U(B.251-252s
Keywords: (3GdEOGQI(B-(3fXe GdeYdheGJs